Modern approaches to the treatment of chronic urticaria - Alexey V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2023)
The article provides modern definitions and classification of urticaria. The general provisions of the treatment of chronic urticaria, the treatment of which is often very difficult, are outlined. The main provisions of the treatment of urticaria were formulated, according to which the patient should be treated until the rash is completely resolved. In chronic urticaria, it is necessary to identify and eliminate the causes of dermatosis; avoid exposure to identified triggers; increase tolerance; pharmacological treatment should be aimed at preventing the release of mast cell mediators and/or the effects of mast cell mediators. The goal of treatment should be to relieve the symptoms of urticaria as completely as possible, taking into account the safety and quality of life of the patient in each individual case. The importance of identifying and addressing underlying causes and avoiding identified triggers is emphasized. The therapy algorithm is considered in detail, including 4 lines according to the European guidelines and domestic clinical guidelines. Particular attention is paid to the treatment of various subtypes of chronic urticaria. A comparative description of the most effective antihistamines is given.